The role of Market Orientation and Innovation in Improving Business Performance of the Banking Industry - Milani, Arman Mohajer; Salavati, Shahram (European Journal of Sustainable Development, 2018)
This research aims to investigate the mediating role of innovation in the relationship between marketing orientation and business performance of the banking industry. Data were collected through a questionnaire from directors and deputies at Sina Bank branches in Tehran. Reliability of the questionnaire before distribution was calculated based on Cronbach's alpha method and necessary corrections were made. Structural equation modeling was used to analyze the data. The results indicated that there is a significant relationship relationship between market orientation and business performance with regard to the role of mediator of innovation and tendency to learn in branches of Sina Bank in Tehran. There is a significant relationship between market orientation and business performance, with regard to the role of mediators of innovation and tendency to learn in Sina Bank branches in Tehran. There is a significant relationship between market orientation and tendency to learn, there is a significant relationship between market orientation and innovation. There is a significant relationship between tendency to learn and innovation; there is a significant relationship between innovation and business performance; mediator innovation is the relationship between market orientation and business performance. Tendency to learn is the mediator between innovation and market orientation. Moreover, the results show that there is no significant relationship between market orientation and business performance. The most intense relationship is related to market orientation and tendency to learn while the weakest is observed between market orientation and business performance with regard to mediating role of innovation and the tendency to learn. Keywords: Market orientation, business performance, Tendency to learn, Innovation